Performansi Jaringan TCP/IP Menggunakan Metode VRRP, HSRP, dan GLBP - Pracasitaram, I Gede Made Surya Bumi; Sastra, Nyoman Putra; Wirastuti, NMAE Dewi (Majalah Ilmiah Teknologi Elektro; Vol 18 No 1 (2019): (Januari - April) Majalah Ilmiah Teknologi Elektro, 2019)
Nowadays the use of TCP / IP networks at this time is very crucial, where almost all companies, government and private agencies depend on this network to facilitate business and communication to grow up the companies. Network failure caused by link failure or devices failure is very intolerable because it will disrupt business and communication activities that last 24 days, 7 days a week. To overcome the problem of network failure this study is using three methods which will be discussed, namely: VRRP, HSRP and GLBP. It is expected that the use of these three methods can provide a solution to overcome network failures for the smooth running of business and telecommunications activities. The results of the tests that have been done, GLBP method looks better when compared to the VRRP and HSRP methods, especially in testing packet loss and throughput. Keywords—GLBP, HSRP, Load Balancing,TCP/IP, VRRP